A neuropsychological instrument adding to the description of patients with suspected cortical dementia: the Milan overall dementia assessment. Issue 12 (December 1994) - Brazzelli, M; Capitani, E; Della Sala, S; Spinnler, H; Zuffi, M
Abstract : A new, short, neuropsychologically oriented test for dementia assessment–the Milan Overall Dementia Assessment (MODA)–is described. Age and education adjusted norms based on 217 healthy controls are given. A validation study on 312 outpatients suspected of dementia (121 with probable Alzheimer's disease) showed that the MODA differentiated patients with cognitive impairment from normal subjects more effectively than did the DSM III-R. The correlation between the MODA and the mini mental state examination was 0.63 in controls and 0.84 in patients with Alzheimer's dementia. The MODA test-retest reliability was 0.83. The test proved to be well suited to longitudinal studies.